Implementasi Model Pembelajaran Konsiderasi Sebagai Upaya Penanaman Karakter Anak Di RA Al-Washliyah Kisaran Kabupaten Asahan - Rahman, Mhd Habibu (Universitas Hamzanwadi, 2019)
This paper presents the application of the consideration learning model and the importance of planting character to children from an early age. The consideration learning model is a learning model that emphasizes attitudes as a result of learning and the process of changing beliefs, attitudes and values towards a better direction. This study aims to find out the application of the consideration model of learning in early childhood, and what methods are used by teachers to instill the character of early childhood. Sources of data in this study include principals, class teachers, and children. Data collection is done by observation, interviews, and documentation. Data analysis is done by data reduction, data presentation, and conclusion drawing. Based on the results of the study it can be concluded that the consideration learning model applied at RA Al-Washliyah Kisaran Asahan Regency is to treat each child with respect, stay away from authoritarianism, create togetherness, help each other, respect each other. Planting characters using the method of storytelling, role playing, exemplary, and habituation